2014
DOI: 10.4236/cm.2014.52016
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Antioxidant Effects of <i>Salvia officinalis</i> L. Hydroalcoholic Extract in Male Rats

Abstract: The antioxidant effects of Salvia officinalis L. hydroalcoholic extract and also its hepatoprotective effects in male rats were evaluated. Salvia officinalis L. extract was administered intraperitoneally for 28 days. Serum levels of aspartate aminotransferase, alanine transferase and alkaline phosphates in rats coadministered with both isoniazid (INH) 50 mg/kg and Salvia officinalis L. extract at 250 mg/kg showed significant reduction when compared to INH group, but administration of Salvia officinalis L. extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Recently, another study reported that sage essential oil reduces oxidative stress and the toxic effects in liver injury which was induced by vanadium metal in rat liver [31]. Similarly, another study observed that sage protected the liver against isoniazid-induced hepatic toxicity [51]. In this regard, the Salvia officinalis leaves' methanolic extract also protected the liver injury induced by aflatoxins [52].…”
Section: In Vivo Hepatoprotective Effectmentioning
confidence: 99%
“…Recently, another study reported that sage essential oil reduces oxidative stress and the toxic effects in liver injury which was induced by vanadium metal in rat liver [31]. Similarly, another study observed that sage protected the liver against isoniazid-induced hepatic toxicity [51]. In this regard, the Salvia officinalis leaves' methanolic extract also protected the liver injury induced by aflatoxins [52].…”
Section: In Vivo Hepatoprotective Effectmentioning
confidence: 99%
“…Significant reductions in the total cholesterol, triglycerides, low-density lipoprotein, and C-reactive protein was found, along with a decrease in body weight and abdominal fat mass [93]. Several other studies illustrated various positive metabolic changes in animal studies [94,95]. A non-randomized crossover trial on six women who consumed 600 mL of sage infusion per day during 4 weeks, followed by 2 weeks of a wash-out period, found no effect on plasma glucose, but the level of LDL and the total cholesterol lowered, while HDL increased [96].…”
Section: Sage and Health Benefitsmentioning
confidence: 99%
“…The highest antioxidant activities of sage were discovered in the methanolic extract, followed by water infusion and decoction [ 84 ]. The hydroalcoholic extract of sage exhibited high antioxidant activity [ 85 ]. For example, earlier study has shown that the hydroalcoholic extract of sage has hepatoprotective action against isoniazid-induced hepatic damage in rats.…”
Section: Herbal Infusions Antioxidant and Anticancer Capacitiesmentioning
confidence: 99%